Contaminants of emerging concern in Finnish waterbirds - Ask, Amalie Vigdel (fi=Turun yliopisto|en=University of Turku|, 2025)
Chemical pollution of the environment is widespread with detrimental effects on wildlife. Currently, more than 350 000 different chemicals or mixtures thereof are registered on the global market and the chemical industry is expected to continue its growth. This necessitates an expansion of which chemicals wildlife toxicology studies target. In this thesis, I examine the occurrence and concentrations of 73 contaminants in waterbirds. In Chapter I, I investigate whether classes of common environmental pollutants, viz. bisphenols, benzophenones, phthalate metabolites, benzotriazoles, benzothiazoles, parabens, triclosan, and triclocarban are present in the plasma of breeding female common eiders (Somateria mollissima) from a colony in the Archipelago Sea, Finland. I detected 21 of the 58 contaminants targeted, with bisphenol A and benzophenone-3 being dominant in terms of concentrations and detection frequencies. I found evidence of late-breeding females having higher concentrations of some contaminants compared to early-breeding females. In Chapter II, I continued my investigation of the aforementioned contaminant families in the eider by collecting whole clutches and plasma samples from the mother. I found no evidence of the egg laying order affecting the concentrations of contaminants in the eggs. While 9 contaminants were detected in both eggs and plasma, 8 were detected in only eggs and 4 only in plasma. This, combined with overall higher detection frequencies of many of the contaminants in eggs compared to plasma, suggests that eggs may be a more suitable matrix for monitoring the targeted contaminants in eiders. Finally, in Chapter III, I examined the occurrence of neonicotinoids in plasma samples from female common goldeneyes (Bucephala clangula) breeding across Finland. Interestingly, I did not detect any of the seven targeted neonicotinoids—nor their transformation products—in any of the sampled goldeneyes. While the limits of detection (LOD) may have been too high to detect low levels of neonicotinoids in the females, the LODs were sufficiently low to assess whether neonicotinoid exposure poses a major risk to the goldeneyes. This thesis reveals that waterfowl, as exemplified by the eider, are exposed to a cocktail of contaminants, many of which are severely understudied and more scientific attention should be given to expanding our knowledge of the behaviour and fate of these contaminants in wildlife and in the environment.

Huolta aiheuttavat uudet haitta-aineet Suomen vesilinnuissa Ympäristön kemikalisoituminen on laaja ongelma, joka vaikuttaa haitallisesti eliöihin. Tällä hetkellä markkinoilla on yli 350 000 rekisteröityä kemikaalia tai kemiallista seosta, ja kemianteollisuuden odotetaan edelleen kasvavan kansainvälisesti. Tämä tekee tarpeelliseksi laajentaa myös ympäristötoksikologiassa tutkittavien kemikaalien määrää. Tässä väitöskirjassa tutkin 73 haitta-aineen esiintyvyyttä ja pitoisuuksia vesilinnuissa. Luvussa I tutkin ympäristössä yleisesti esiintyvien haitallisten aineiden esiintymistä Saaristomerellä pesivien naarashaahkojen (Somateria mollissima) veriplasmassa. Tutkittavat aineryhmät ja aineet olivat bisfenolit, bentsofenolit, ftalaattien metaboliitit, bentsotriatsolit, bentsotiatsolit, parabeenit, triklosaani ja triklokarbaani. Tutkitusta 58:sta haitta-aineesta haahkoissa esiintyi 21, joista bisfenoli-A:n ja bentsofenoli-3:n pitoisuudet ja esiintyvyys olivat suurimmat. Joidenkin tutkittujen aineiden pitoisuudet vaikuttivat olevan suurempia myöhään pesivissä haahkanaaraissa verrattuna aikaisemmin pesinnän aloittaviin naaraisiin. Luvussa II jatkoin edellä mainittujen haitta-aineryhmien tutkimusta haahkoissa keräämällä kokonaisia pesällisiä munia sekä plasmanäytteet ne munineilta emoilta. En löytänyt viitteitä siitä, että munimisjärjestys vaikuttaisi munien haitta-ainepitoisuuksiin. Havaitsin yhdeksää tutkituista aineista sekä munissa että plasmassa, kahdeksaa ainetta vain munissa, ja neljää vain plasmassa. Koska useita tutkittuja aineita esiintyi useammin munissa kuin plasmassa, vaikuttaa että munat soveltuvat plasmaa paremmin tutkittujen haitta-aineiden seurantaan haahkoissa. Luvussa III tutkin neonikotinoidien esiintymistä eri puolilla Suomea pesivien naarastelkkien (Bucephala clangula) plasmassa. En havainnut yhtään tutkituista seitsemästä neonikotinoidista tai niiden trans-formaatiotuotteista telkissä. Vaikka aineiden toteamisrajat olivat mahdollisesti liian korkeita matalien neonikotinoidipitoisuuksien havaitsemiseen, toteamisrajat olivat tarpeeksi alhaiset neonikotinoidien telkille aiheuttaman terveysriskin arviointia varten. Väitöskirjani osoittaa, että vesilinnut, esimerkkinä haahka, altistuvat samanaikaisesti usealle haitta-aineelle, joista usean haittavaikutuksia ei ole tutkittu tarpeeksi. Tulevaisuudessa tarvitaankin lisää tutkimusta näiden haitta-aineiden käyttäytymisestä ja vaikutuksesta eliöissä ja ympäristössä.